A new look at intergenerational mobility in Germany compared to the US - Daniel D. Schnitzlein (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Motivated by contradictory evidence on intergenerational mobility in Germany, I present a cross-country comparison of Germany and the US, reassessing the question of whether intergenerational mobility is higher in Germany than the US. I can reproduce the standard result from the literature, which states that the German intergenerational elasticity estimates are lower than those for the US. However, based on highly comparable data, even a reasonable degree of variation in the sampling rules leads to similar estimates in both countries. I find no evidence for nonlinearities along the fathers' earnings distribution. In contrast, the analysis shows that mobility is higher for the sons at the lowest quartile of the sons' earnings distribution in both countries. In Germany this result is mainly driven by a high downward mobility of sons with fathers in the upper middle part of the earnings distribution. The corresponding pattern is clearly less pronounced in the US.
Keywords: J62; 330; intergenerational mobility; SOEP; CNEF; Germany; US